Evaluating the Use of Mindfulness and Yoga Training on Forensic Inpatients: A Pilot Study - Spinelli, Christina; Paradis-Gagné, Etienne; Per, Megan; Fleischmann, Matthew H.; Manova, Viktoriya; Wallace, Aimée; Khoury, Bassam (Frontiers in Psychiatry, 2020)
Forensic inpatients (i.e., individuals found not responsible for a criminal offence on account of mental illness) represent an often marginalized and difficult-to-treat population. This has led to the need for research exploring the effectiveness of novel interventions. A Canadian forensic hospital has developed an eight-week mindfulness and yoga training program (MTP). This pilot study examined the potential effects of this program on patients’ mindfulness, stress, and use of cognitive and emotion regulation strategies. A sample of 13 forensic inpatients (male = 92%) participating in the MTP program completed self-report measures assessing dispositional mindfulness, perceived stress, and use of cognitive emotion regulation strategies at baseline, post-intervention, and a three-month follow-up. Repeated measure ANOVAs found a significant increase in the describe facet of mindfulness (p = .03) with a large effect size (ηp2 = .26) and a significant decrease in stress (p = .003) with a large effect size (ηp2 = .39). Pairwise comparisons revealed medium to large significant changes between baseline and post-intervention for both the describe facet (p = .03, Hedge’s g = .55) and stress (p = .003, Hedge’s g = .70). However, comparisons were insignificant between baseline and follow-up. No significant main effects were found on the use of cognitive emotion regulation strategies. This pilot study offers preliminary support for the use of the MTP as an adjunctive therapy in forensic in-patient treatment. Further investigation is needed into the long-term impacts of this training.